PENGARUH PENGANGGARAN PARTISIPATIF PADA KINERJA MANAJERIAL DENGAN KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN SEBAGAI PEMODERASI - Agustina Windasari, Putu; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This research aims to examine the interaction budgetary participation on managerial performance withthe characteristic of management accounting system as moderating variables. This research is conducted on 34 Satuan Perangkat Kerja Daerah (SKPD) Kabupaten Badung and  the population are managers in SKPD Kabupaten Badung. The number of sample is 86 by using proportionate stratified random sampling method. Data were collected via questionnaires survey method, obtained through to the respondents and analyzed with moderated regression analysis.The result reveals that participative budgeting has positive influence to managerial performance and integration weaken the relationship between budgetary participation and managerial performance.
Keywords: budget participation, managerial performance, the characteristic of management accounting system